Evaluating the quality of HPV vaccine-related information on the Portuguese Internet - Michael Zarnowski Passos; Agnaldo Lopes da Silva-Filho; Wladmir Cardoso Brandão; Mariana Furtado Meinberg; Rogéria Andrade Werneck (Taylor & Francis Group, 2022)
Human papillomavirus (HPV) is considered the second largest human carcinogen after tobacco and is responsible for 5% of all cancers, 10% of cancers in women, and 15% of all cancers in developing countries. Among these, cervical cancer is the most prevalent. An HPV vaccine has recently been developed to provide primary protection against the viral infection. In 2014, Brazil's National Immunization Program (Programa Nacional de Imunizações, PNI) started making a quadrivalent vaccine available to the public. However, after 2014, the vaccine coverage dropped and did not reach the PNI's targets. Among other factors, this low uptake was due to the quality of information on the Internet. Using Google Trends, the main search terms used to search for vaccine-related information on the Internet were identified. The content of the identified websites was analyzed using the DISCERN instrument and their reach was determined using their page authority score. Most of the texts analyzed were not of high quality. The data that most commonly reach the lay public are from sites that lack scientific rigor. We found a weak correlation between the DISCERN and page authority scores. Based on our analysis, we inferred that the information that reaches the user is not always the most accurate and can lead to harmful decisions on vaccination. The content that reaches the user most easily is not always of sound quality. New analyses are important, especially on the impact of social networks that present even fewer criteria in publications and are more easily accessible.